Effectiveness of cognitive behavioral therapy based on religion on depression and quality of life in patients with HIV/AIDS - Hamid N; Kaviany Brojeny A (مجله دانشگاه علوم پزشکی گرگان, 2016)
Background and Objective: Cognitive behavioral therapy based on religion can increase the religious mind. This study was done to evaluate the effectiveness of cognitive behavioral therapy based on religion on depression and quality of life in patient with HIV/AIDS.